Tamoxifen treatment adherence assessment by women with breast cancer - Caroline Oliveira Rangel; Christiane de Fátima Colet; Vanessa Adelina Casali Bandeira; Gabriela Tassotti Gelatti; Rodrigo Fernando dos Santos Salazar; Roberta Cattaneo Horn (Universidade de Santa Cruz do Sul, 2020)
Justification and objectives: oral antineoplastic therapy has advantages compared to other therapies for the treatment of cancer, as it is administered at home, in a simple and fast way. However, this therapy increases patients' responsibility for their treatment, and compliance is critical to its effectiveness. Few studies are evident regarding pharmacotherapeutic follow-up in oral antineoplastic therapy. In this context, this study seeks to assess adherence to tamoxifen treatment in women with breast cancer, before and after pharmacotherapeutic follow-up. Methods: this is a randomized, quantitative clinical study. Data collection was carried out for six months. Random randomization was divided into a control group and a follow-up group, with the follow-up subdivided into before and after follow-up. The follow-up group received individual pharmaceutical interventions monthly. Adherence was assessed by The Brief Medication Questionnaire, Brazilian version and drug-related problems as to necessity, effectiveness, and safety. Results: after pharmaceutical follow-p, a difference was observed between the follow-up group and the control group regarding physical activity (p=0.043), treatment adherence (p=0.006), reduction of side effects (p=0.003) and associated diseases (p=0.002). The most frequent drug-related problems were safety and adherence, for which 54 pharmaceutical interventions were performed. The side effects described by patients mainly affected the genital system and gastrointestinal tract. Conclusion: it was evident that pharmacotherapeutic follow-up effectively contributed to adherence to treatment with tamoxifen and the pharmaceutical interventions performed contributed to prevention and reduction of drug-related problems.